Physiological and Biochemical Dissection Reveals a Trade-Off between Antioxidant Capacity and Heat Tolerance in Bread Wheat (Triticum aestivum L.) - Mohammed Mohi-; Nurealam Siddiqui; Motiar Rohman; S. V. Krishna Jagadish; Jalal Uddin Ahmed; Mohamed M. Hassan; Akbar Hossain; Tofazzal Islam (MDPI AG, 2021)
Heat stress alters photosynthetic components and the antioxidant scavenging system, negatively affecting plant growth and development. Plants overcome heat stress damage through an integrated network involving enzymatic and non-enzymatic antioxidants. This study aimed to assess physiological and biochemical responses in contrasting thermo-tolerant wheat varieties exposed to 25 °C (control) and 35 °C (heat stress), during the seedling stage. Our results revealed a substantial decrease in the photosynthetic pigments, carotenoids, anthocyanin content, and increased membrane injury index, malondialdehyde, methylglyoxal (MG), H2O2 contents and lipoxygenase activity compared to non-stress wheat seedlings. The heat-tolerant variety BARI Gom 26 ("BG26") maintained higher cellular homeostasis compared to the heat susceptible variety Pavon 76 ("Pavon"), perpetuated by higher accumulation of proline, glycine betaine, ascorbate-glutathione cycle associated enzymes, reduced glutathione and ascorbate concentration in plant cells. Significantly lower levels of MG detoxification and antioxidant activities and ascorbate-glutathione cycle-related enzymatic activities lead to increased susceptibility in variety "Pavon". Hierarchical clustering and principal component analysis revealed that variety "BG26" possess a combination of biochemical responses tailoring antioxidant activities that induced a higher level of tolerance. Taken together, our results provide a pipeline for establishing a trade-off between antioxidant capacity and heat tolerance to facilitate functional genomics and translational research to unravel underlying mechanisms to better adapt wheat to heat stress.